Tamizaje universal de hipoacusia en el recién nacido - Alvo V., Andrés; Der M., Carolina; Délano R., Paul H. (Revista Hospital Clínico Universidad de Chile, 2010)
Neonatal hearing loss affects 1-3 from every 1000 live newborns. For optimal language and social development, proper diagnosis and treatment must be established before the first 6 months of age. In Chile, screening for hearing loss is only performed on high-risk newborns weighting less than 1500 grams. However, about half of the newborns with hearing loss have no risk factors. Given the importance of this disability and the fact that it can be effectively diagnosed, a universal detection program for hearing loss becomes necessary. Furthermore, effective treatments for hearing loss, like hearing aids and cochlear implants are available in several institutions of our country, including the Clinical Hospital of the University of Chile. Worldwide, the most used screening methods are otoacoustic emissions and auditory brainstem evoked responses, the former, a test that detects the acoustic energy generated by the outer hair cells of the cochlea in response to a brief sound, and the latter a test that measures neural responses of the central auditory pathway. Both are objective and non-invasive techniques. Here we review evidences that support the need of creating a universal newborn hearing screening program in Chile.